Figurative Language Analysis of “Berita Kepada Kawan” by Ebiet G. Ade Among UIN Bandung Students - Aqil Rudya Alam; Otong Setiawan Djauhari (INDO PUBLISHING, 2025)
This study investigates the use of figurative language in the song “Berita Kepada Kawan” by Ebiet G. Ade, focusing on the widespread misinterpretation of its meaning by listeners. Many audiences perceive the song literally, overlooking the deep symbolic messages embedded in its lyrics. The purpose of this article is to reveal the figurative language used in the song and highlight how different individuals may interpret the same lyrics differently, often diverging from the songwriter’s intended message. Employing a qualitative research method, the study involved a participatory approach through an online questionnaire distributed via Google Forms to 26 respondents. The findings indicate a significant variation in interpretation among listeners, with a majority failing to grasp the figurative elements and underlying messages of the song. These results suggest that lyrical content, especially in poetic or symbolic forms, often requires contextual understanding to avoid misinterpretation. The study concludes that a lack of awareness regarding figurative language contributes to misunderstanding song lyrics, which may diminish the impact of the songwriter’s message. It recommends further research on public perception of figurative language in music and the role of educational tools in enhancing lyrical comprehension.